Price or variety? An evaluation of mergers effects in grocery retailing - Elena Argentesi; Paolo Buccirossi; Roberto Cervone; Tomaso Duso; Alessia Marrazzo (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
Assortment decisions are key strategic instruments for firms responding to local market conditions. We assess this claim by studying the effect of a national merger between two large Dutch supermarket chains on prices and on the depth as well as composition of assortment. We adopt a difference-in-differences strategy that exploits local variation in the merger's effects, controlling for selection on observables when defining our control group through a matching procedure. We show that the local change in competitive conditions due to the merger did not affect individual products' prices but it led the merging parties to reposition their assortment and increase average category prices. While the low-variety and low-price target's stores reduced the depth of their assortment when in direct competition with the acquirer's stores, the latter increased their product variety. By analyzing the effect of the merger on category prices, we find that the target most likely dropped high priced products, while the acquirer added more of them. Thus, the merging firms reposition their product offerings in order to avoid cannibalization and lessen local competition. Further, we show that other dimensions of heterogeneity, such as market concentration, whether a divestiture was imposed by the Dutch competition authority, and the re-branding strategy of the target stores, are important for explaining the post-merger dynamics. A simple theoretical model of local-market variety competition explains most of our findings.
Keywords: L1; L41; L66; L81; D22; K21; C23; 330; Variety; Assortment; Mergers; Ex-post Evaluation; Retail sector; Supermarkets; Grocery